The legal phenomenon of "complience-service" in commercial activities: international experience and development prospects - Матвєєв, Петро Сергійович; Матвєєв, П. С.; Матвеев, Петр Сергеевич; Matvieiev, Petro S.; Мурзановська, Аліна Владиславівна; Мурзановська, А. В.; Мурзановская, Алина Владиславовна; Murzanovska, Alina V.; Іванченко, Ольга Миколаївна; Іванченко, О. М.; Иванченко, Ольга Николевна; Ivanchenko, Olha M.; et al. (Editorial Primmate S. A. S., 2021)
In the context of globalization, the company must meet international standards to do business with foreign partners. For the commercial activity to meet the requirements of legality, ethics, transparency, for you to be considered a reliable counterparty, it is necessary to apply compliance. This concept means that an entity complies with the requirements of the law, rules, and standards of doing business. The purpose of the study was to analyze the peculiarities of the application of compliance from a legal point of view, to take into account foreign experience, to investigate how compliance is used in Ukraine. The authors used the system-functional method, formal-legal method, methods of analysis, and synthesis. As a result of the study, it was found that compliance is an essential tool for systematizing and conducting business under the requirements of regulations, internal regulations, ethical requirements. The application of compliance has several functions, among which are the elimination of shortcomings in the enterprise, standardization, maintaining an impeccable business reputation, resolving conflicts of interest, standardizing the behavior of employees, company officials, their interaction with external entities, maintaining corporate culture, and anti-corruption. It was also found that a compliance service such as due diligence is useful in the contractual process and can also be used to forecast economic performance.

В умовах глобалізаційних процесів підприємство має відповідати міжнародним стандартам для того, щоб вести бізнес із закордонними партнерами. Для того, щоб комерційна діяльність відповідала вимогам законності, етичності, прозорості, для того, щоб вас вважали надійним контрагентом, необхідно застосовувати комплаєнс. Це поняття означає відповідність суб’єкта господарювання вимогам законодавства, правилам та стандартам ведення бізнесу. Метою дослідження було проаналізувати особливості застосування комплаєнсу з юридичної точки зору, врахувати закордонний досвід, дослідити, як комплаєнс застосовується в Україні. Для цього ми використали системно-функціональний метод, формально-юридичний метод, прийоми аналізу та синтезу. Автори використали системно-функціональний метод, формально-юридичний метод, прийоми аналізу та синтезу. У результаті дослідження було встановлено, що комплаєнс є важливим інструментом для систематизації та ведення бізнесу відповідно до приписів нормативно-правових актів, документів внутрішнього розпорядку, етичних приписів. Застосування комплаєнсу переслідує ряд функцій, одними з яких є усунення недоліків в роботі підприємства, стандартизація, підтримка бездоганної ділової репутації, врегулювання конфлікту інтересів, у нормування поведінки співробітників, посадових осіб компанії, їх взаємодії з зовнішніми суб’єктами, підтримання корпоративної культури, протидія корупції. Також було встановлено, що така комплаєнс-послуга як due diligence є корисною в договірному процесі, а також може використовуватися для прогнозування результатів економічної діяльності.
Matvieiev P. The legal phenomenon of «complience-service» in commercial activities: international experience and development prospects / P. Matvieiev, A. Murzanovska, O. Ivanchenko // Amazonia Investiga. - Vol. 10. - Iss. 45. – Editorial Primmate S. A. S., 2021. - Р. 198-207.
Keywords: compliance; due diligence; ethical norms; reputation; business; комплаєнс; due diligence; етичні норми; репутація; бізнес; Research Subject Categories::LAW/JURISPRUDENCE